Corrosion protection of stainless steel by polysiloxane hybrid coatings prepared using the sol-gel process - Sarmento, V. H. V. [UNESP]; Schiavetto, M. G. [UNESP]; Hammer, Peter [UNESP]; Benedetti, Assis Vicente [UNESP]; Fugivara, Cecilio Sadao [UNESP]; Suegama, P. H. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Elsevier B.V. Sa, 2010)
Polysiloxane hybrid films were deposited on 316 L stainless steel substrates by dip-coating in a sol prepared by acid-catalyzed hydrolytic co-polycondensation of tetraethoxysilane (TEOS) and 3-methacryloxy propyltrimethoxysilane (MPTS), followed by radical polymerization of methacrylic moieties. Structural features of the polysiloxane hybrids were studied using (13)C and (29)Si nuclear magnetic resonance (NMR), X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA), as a function of the TEOS/MPTS ratio, which ranged between 0 and 2. The efficiency of corrosion protection of hybrid-coated stainless steel was investigated by X-ray photoelectron spectroscopy (XPS), potentiodynamic polarization curves and electrochemical impedance spectroscopy (EIS) after immersion of the material in acidic and neutral saline aqueous solutions. The NMR and TGA results indicated a high degree of polymerization and polycondensation (85%) for the hybrid film with a TEOS/MPTS ratio of 2, as well as elevated thermal stability of 410 C and excellent adhesion. The XPS analysis confirmed the hybridized structure of the polysiloxane network, and showed that no corrosion-induced changes had occurred on the coated steel surface after 3 weeks of immersion in 3.5% NaCl solution. Potentiodynamic polarization curves showed that the hybrid coating prepared using a TEOS/MPTS ratio of 2 yielded the best anti-corrosion performance. It acts as an efficient physical barrier, increasing the total impedance and reducing the current densities by 2 orders of magnitude, compared to the bare electrode. The impedance results obtained for the two electrolytes were discussed based on the electrical equivalent circuits used to fit the experimental data. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Hybrid coatings; Corrosion; Structure; Stainless steel 316 L